2021
DOI: 10.1080/00472778.2021.1938097
|View full text |Cite
|
Sign up to set email alerts
|

Why I persist while others leave? Investigating the path from passion to persistence in entrepreneurship

Abstract: Although research affirms that entrepreneurial passion (EP) is an important predictor of entrepreneurial persistence, much less is known of the underlying processes through which EP leads to entrepreneurial persistence. Drawing upon the broaden-and-build theory of positive emotions, this study uncovers the mediating effects of entrepreneurial selfefficacy (ESE) and the moderating role of proactive personality between the relationship of EP and entrepreneurial persistence. The results of survey data from 215 sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 116 publications
1
17
0
1
Order By: Relevance
“…These features certainly help entrepreneurs in Asia to create tolerant and harmonious corporate cultures, resulting in higher success rates and satisfied employees and customers (Deng et al, 2011). Research shows female entrepreneurs to be more persistent than male entrepreneurs, paying more attention to long-term benefits and the development of the company (Kiani et al, 2021). They strive for their business ideals despite temporary difficulties and setbacks, while making every business decision very carefully and pursuing realistic objectives.…”
Section: The Influence Of Cultural Valuesmentioning
confidence: 99%
“…These features certainly help entrepreneurs in Asia to create tolerant and harmonious corporate cultures, resulting in higher success rates and satisfied employees and customers (Deng et al, 2011). Research shows female entrepreneurs to be more persistent than male entrepreneurs, paying more attention to long-term benefits and the development of the company (Kiani et al, 2021). They strive for their business ideals despite temporary difficulties and setbacks, while making every business decision very carefully and pursuing realistic objectives.…”
Section: The Influence Of Cultural Valuesmentioning
confidence: 99%
“…Furthermore, entrepreneurship often takes time, requiring multiple starts, and continued effort in the face of obstacles and failures (Caliendo et al. , 2020; Kiani et al , 2021; Millán et al. , 2014).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Thus, while it is important to hone in on this dynamic among female entrepreneurs, existing research have largely overlooked this cohort as indicated by the skewed gender ratios in empirical research samples on entrepreneurial passion. It is notable that male samples are generally much larger than female samples (de Mol et al, 2016(de Mol et al, , 2020Stroe et al, 2019;Luu and Nguyen, 2020;Murnieks et al, 2020;Kiani et al, 2021;Su et al, 2022), and research conclusions are more connoted to male entrepreneurs. This study uses follow-up survey data of 88 Chinese female entrepreneurs at three points in time over 5 months, focuses on dynamic changes in these women's entrepreneurial passion, and adds a unique perspective to the body of research on female entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, their entrepreneurial practices are more influenced by family or domestic factors (Jennings and McDougald, 2007;Hsu et al, 2016), and this often limits their entrepreneurial passion (Murnieks et al, 2020). It should be noted that there is embedded gender bias in existing empirical research on entrepreneurial passion in that male samples are considerably larger than female samples (de Mol et al, 2016;Murnieks et al, 2020;Kiani et al, 2021). In some cases, male samples are twice as large as female samples (Stroe et al, 2019;de Mol et al, 2020;Luu and Nguyen, 2020;Su et al, 2022), making traditional research conclusions on entrepreneurial passion highly skewed to male entrepreneurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation